2022
DOI: 10.51505/ijebmr.2022.6608
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Collaborative Learning in the Online Education

Abstract: Collaboration or teamwork is indispensable in today’s workplace. The continual and increasingly rapid change in the external environment requires professionals equipped with unique skill sets to work together and solve problems collaboratively. It is the higher education institution’s responsibility to prepare students for the necessary skills expected by the employers. Collaborative learning is an active learning approach that two or more students team up toward common goals. The knowledge and product are cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…However, there was a lack of interaction with patience and ICT technical glitches experienced during learning. Online learning may reduce opportunities for interaction and collaboration among students, hindering the development of teamwork and interpersonal skills (Lu & Smiles, 2022). Lecturers face challenges in promoting engagement, facilitating group work, and fostering a sense of community in virtual environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there was a lack of interaction with patience and ICT technical glitches experienced during learning. Online learning may reduce opportunities for interaction and collaboration among students, hindering the development of teamwork and interpersonal skills (Lu & Smiles, 2022). Lecturers face challenges in promoting engagement, facilitating group work, and fostering a sense of community in virtual environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mannisto et al (2020) conducted a systematic literature review of collaborative learning in digital environments and found that it enhanced nursing student problem-solving skills, competence, and engagement in learning. Likewise, in other disciplines and contexts collaborative learning and problem solving is considered an effective strategy for improving learner cognitive, social, and affective skills (Lai & Wong, 2021;Lu & Smiles, 2022).…”
Section: Degree Of Collaboration: a Necessary Addition To The Criteri...mentioning
confidence: 99%
“…As a means of overcoming the above issues, according to the researchers, in order to teach vocabulary and reading comprehension, teachers must use collaborative learning that is integrated into a semantic mapping strategy. which requires students to interact and work together in groups that have a small size, made up to four-members of different level of knowledge [26] [27]. Through group collaborative learning integrated with semantic strategy, students can construct a deeper understanding and reach a consensus [28] [29].…”
Section: Introductionmentioning
confidence: 99%